Sirtuin family: a link to metabolic signaling and senescence - Kyrylenko, S; Baniahmad, A (Current medicinal chemistry, 2010)
A vast collection of data obtained during the last decade supports the view on sirtuins as sensors of actual cellular metabolic state being involved in cell cycle progression, apoptosis/survival decision making, longevity, inflammation etc. Moreover, sirtuins themselves can control metabolism through their ability to consume NAD(+). In turn, cellular NAD parameters may affect the generation of ATP, a main cellular currency of energy. Therefore, sirtuins became recognized as critical affectors of cellular metabolism which participate in fat mobilization, gluconeogenesis, caloric restriction etc. Cellular senescence is viewed as a mechanism to restrict excessive cell growth when it is unnecessary or harmful. It is therefore necessary to understand the mechanism of senescence to design new approaches to combat cancer. Growth in turn depends on metabolism as it requires energy. Therefore, in this review, we address the connection of sirtuins to senescence through their participation in the regulation of metabolic and biochemical parameters and related signaling.
Keywords: Aging; lidé; Signal Transduction; Stilbenes; signální transdukce; antiflogistika nesteroidní; stilbeny; sirtuiny; Humans; NAD; Anti-Inflammatory Agents, Non-Steroidal; Sirtuins; stárnutí